1998
DOI: 10.1063/1.122747
|View full text |Cite
|
Sign up to set email alerts
|

Large tunneling magnetoresistance enhancement by thermal anneal

Abstract: Spin tunnel junctions with tunneling magnetoresistance of 36.5%±0.5%, resistance-area product of 35±6 kΩ×μm2, and junction area between 6 and 75 μm2 were fabricated. The barrier height is 2.5±0.3 eV and the barrier thickness is 7.7±0.3 Å. Large tunneling magnetoresistance (TMR) values are obtained by vacuum anneal (at temperatures from 100 to 240 °C for over 5 h) of junctions prepared with as-deposited TMR of 21%±1.7%, and an as-deposited resistance-area product of 25±6 kΩ×μm2. Two regimes occur during anneal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
69
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(75 citation statements)
references
References 14 publications
6
69
0
Order By: Relevance
“…Annealing experiments of magnetic tunnel junctions have shown that above 210°C the junction ͑magneto͒resis-tance drops severely, indicating that irreversible processes take place in or close to the junction barrier at this temperature. 13 Several Co/Al 2 O 3 /Co junctions were inspected with a scanning electron microscope after breakdown, but no visible sign of damage was found, as is expected when breakdown is a very microscopic event. The location of the short was, however, visualized with the use of a thin liquid crystal film deposited on the junction.…”
Section: Resultsmentioning
confidence: 99%
“…Annealing experiments of magnetic tunnel junctions have shown that above 210°C the junction ͑magneto͒resis-tance drops severely, indicating that irreversible processes take place in or close to the junction barrier at this temperature. 13 Several Co/Al 2 O 3 /Co junctions were inspected with a scanning electron microscope after breakdown, but no visible sign of damage was found, as is expected when breakdown is a very microscopic event. The location of the short was, however, visualized with the use of a thin liquid crystal film deposited on the junction.…”
Section: Resultsmentioning
confidence: 99%
“…[12,13,14,15] On the other hand, for magnetic tunnel junctions, improvements in their performance were obtained with vacuum anneals. [16,17] In this letter we discuss how Al-AlO x -Al tunnel junctions can be completely stabilized, and their characteristics improved by thermal annealing in vacuum. The general trend of increase of R T with the annealing is reproduced.…”
mentioning
confidence: 99%
“…The barriers are known to contain defects, some natural 6 and others of artificial origin. 7,8 Factors such as the barrier roughness 9 and chemical homogeneity 10 have been investigated as well as the specifics of barrier oxidation. 11,12 It is important in the optimization of TMR to understand the oxidation process and in particular how to oxidize the entire Al layer and none of the ferromagnet.…”
mentioning
confidence: 99%